Pengaruh Model Kooperatif Tipe Talking Stick terhadap Hasil Belajar Tematik Terpadu Kelas IV SD - Sri Yanti; Rifda Eliyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study was to determine the effect of the Talking Stick Type Cooperative model on the integrated thematic learning outcomes of grade IV SD 35 Parak Karakah. This type of research is a quasi-experimental design with the form of nonequivalent control group design . The sampling technique used is simple random sampling. The sample in this study was grade IV students of SD Negeri 35 Parak Karakah in class IVA as an experimental class and class IVB as a control class, each of which amounted to 20 students. Based on the results of the study obtained an average value of 50.60 experimental class pretest and 52.45 control class. The average posttest score of the experimental class was 76.60 and the control class was 65.50. Based on the results of the hypothesis test analysis at a significance level of 5%, it was obtained tcount> ttable (2.33> 2.024), so it can be concluded that the Cooperative Type Talking Stick model influences the integrated thematic learning outcomes of students in grade IV SD 35 Parak Karakah